Impact of Transcatheter Aortic Valve Implantation on Thrombin Generation and Platelet Function - Mourikis, Philipp; Dannenberg, Lisa; Zako, Saif; Helten, Carolin; M‘Pembele, René; Richter, Hannah; Hohlfeld, Thomas; Jung, Christian; Zeus, Tobias; Kelm, Malte; Veulemans, Verena; Polzin, Amin (Thrombosis and Haemostasis, 2021)
Background Transcatheter aortic valve implantation (TAVI) is an evolving treatment of severe aortic valve stenosis. However, thromboembolic events such as stroke are common, predominantly early after TAVI. Optimal periprocedural antithrombotic regime is unknown. Especially, as antithrombotic medication enhances bleeding risk, thrombin generation and platelet function are crucial in the pathogenesis of ischemic events. However, the impact of the TAVI procedure on thrombin formation and platelet reactivity is not known by now.Methods We evaluated thrombin levels using thrombin–antithrombin (TAT) complexes and prothrombin fragments (PTFs) using enzyme-linked immunosorbent assay. Furthermore, platelet reactivity was measured via light transmission aggregometry before and 2 hours after TAVI in 198 patients.Results TAT complexes and PTF F1 + 2 substantially increased during TAVI. Postprocedurally, TAT complexes and PTF were significantly higher after TAVI compared with percutaneous coronary intervention due to acute myocardial infarction, while preprocedural TAT complexes and PTF F1 + 2 did not differ. In contrast, platelet reactivity was not altered early after TAVI. Only adenosine diphosphate-induced aggregation was reduced, reflecting preprocedural loading with clopidogrel.Conclusion In this pilot study, we were able to demonstrate that thrombin generation is significantly increased early after TAVI, while platelet function is not affected. Increased thrombin concentrations may contribute to the high risk of postprocedural thromboembolic events. This leads to the hypothesis that extended peri-interventional anticoagulation early after TAVI may be an approach to reduce thromboembolic events.
Keywords: aortic stenosis; platelets; thrombin; transcatheter aortic valve implantation